Persepsi Guru Bahasa Indonesia Terhadap Pengembangan BahanAjar Membaca Intensif Di Smp Negeri 4 Tengaran - MUTTAQIN, JOKO (2016)
The research objective describes Indonesian teachers' perceptions of the development of teaching materials intensive reading in SMP Negeri 4 Tengaran. This research is descriptive qualitative research. The object of this study is a teacher at SMPN 4 Tengaran to the development of teaching materials intensive reading in SMP Negeri 4 Tengaran. Data collection techniques in this study consisted of two steps, namely in-depth interviews, and observation. Subjects in the intensive reading SMP Negeri 4 Tengaran contains about knowledge, values, attitudes, and skills that an act contains messages, information, and illustrations in order to achieve the purpose of learning, teaching materials due to intensive reading is the only major source of learning